Comparison of Tonsillectomy Techniques with Reference to their Histopathologic Healing Patterns - Muhammad Naeem, Waqas Javaid, Raana Amir Akbar, Waseem Ahmad, Sultan Badar Munir, Syed Tauseef Bukhari, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the histopathologic healing patterns after tonsillectomy done by dissection ligation versus electrocautery technique. Setting: ENT Unit II of Fatima Jinnah Medical University Sir Ganga Raam Hospital Lahore Duration: 1st July 2021 to 30th June 2022 Study Design: Randomised control trial Sampling: Total of 106 patients were included and divided into 2 groups with probability simple random sampling. Methods: All patients of 10 to 18 years of age with history and examination that was consistent with recurrent tonsillitis were included. Group A underwent tonsillectomy with dissection-ligation technique and Group B with electrocautery. At 7th post operative day tissue samples were taken from palatopharyngeal arch and sent for histopathologic evaluation and healing was graded as good, fair and poor. Patients with acute inflammatory conditions of tonsil or suspicion of malignancy, post tonsillectomy hemorrhage and those with co morbidities were excluded. Results: Mean age of Group A was 13.79 years and in Group B mean age was 13.54 years. When we calculated the association of inflammation, granulation tissue formation, pattern and orientation of collagen fibers between the two groups, the resulting p value was <0.05 in each category. This shows that all the parameters that favors healing were scored high in Group A. Mean of healing score of each group was also calculated. Mean of healing score of Group A is 10.8302 and of Group B is 9.5849. Practical implication As in our study healing outcomes of tonsillectomy done by dissection ligation technique is better as compared to electrocautery, better healing in dissection method will result in quick recovery and decreasing chances of secondary hemorrhage. Which means that patient can resume regular oral intake early in post operative period. Less inflammation in dissection method will result in less pain and odynophagia and hence improves patient’s comfort and quality of life in immediate post operative period. Conclusion: Dissection ligation technique has better healing outcomes than the electrocautery technique of tonsillectomy. Keywords: Recurrent tonsillitis, tonsillectomy, dissection ligation technique, electrocautery technique, healing outcomes.